(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This paper describes the process of semantization for proper nouns in context in English. Although proper names are typically treated as rigid designators of unique individuals, their content does not remain constant. In fact, proper names often develop secondary or metaphorical or culturally significant meanings beyond their denotative role in discourse. Based on data of literary texts, political speech, journalism, and everyday language, it examines how contextual information influences the connotative content of proper names. These results imply that, in the case of proper names, culture appears to frame semantic and pragmatic enrichment along ideological stances and communicative purposes. The study adds to pragmatics, semantics, and discourse analysis in that it underscores the interplay between linguistic structure and social/cultural context.